2021
DOI: 10.34172/aim.2021.125
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Biological Functions of EPC1 in Nasopharyngeal Carcinoma

Abstract: Background: Comb homolog enhancer 1 (EPC1) gene is one of the important members of epigenetic inhibitor PCG family. It shows carcinogenic potential in a variety of malignant tumors, but the expression and role of EPC1 in nasopharyngeal carcinoma are unclear. The aim of this study was to explore the expression and function of enhancer of polycomb homolog 1 (EPC1) in nasopharyngeal carcinoma (NPC). Methods: The differential expression of EPC1 in the cancer tissues and cell lines of NPC was examined by quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
1
1
Order By: Relevance
“…Therefore, we tried to identify the function of EPC1 as a prognostic biomarker in HNSCC by multiomics integrative analysis. We found that EPC1 might indicate a better overall survival for patients with HNSCC, which was inconsistent with the results of NPC from our study [34]. We considered that one of the reasons might be that the expression data of NPC was not available in TCGA, due to the rarity of NPC in America.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Therefore, we tried to identify the function of EPC1 as a prognostic biomarker in HNSCC by multiomics integrative analysis. We found that EPC1 might indicate a better overall survival for patients with HNSCC, which was inconsistent with the results of NPC from our study [34]. We considered that one of the reasons might be that the expression data of NPC was not available in TCGA, due to the rarity of NPC in America.…”
Section: Discussioncontrasting
confidence: 95%
“…EPC1 is a multicomb homolog 1 (Drosophila) enhancer involved in the regulation of cell growth and transcription [31]. EPC1 anomalies may be involved in ossifying fibromyxoid tumors [15], endometrial stromal sarcoma [32], pancreatic cancer [33], and nasopharyngeal carcinoma (NPC) [34]. However, the effect of this gene on the survival prognosis of HNSCC patients has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Third, knockdown of either EPC1 or EPC2 or both restrains cell proliferation in K562 cells. These observations are consistent with the reports that EPC1 or EPC2 are involved in cell cycle progression 26 , 52 and cell proliferation 53 in yeast and mammalian cells, and unveil the essential roles of EPC1 and EPC2 in HSPC proliferation. Knockdown of EPC1 or EPC2 induced cell apoptosis in K562 cells rather than in embryonic HSPCs, not only agreeing with the reports that knockdown of EPC1 and/or EPC2 induced apoptosis in AML cells, 20 but also suggesting that roles of EPC1 and EPC2 in apoptosis are different between in vivo and in vitro cells.…”
Section: Discussionsupporting
confidence: 93%